Mobilising citizen scientists to monitor rapidly changing acid sulfate soils. Issue 2 (2nd July 2016) - Thomas, Mark; Richardson, Carole; Durbridge, Regina; Fitzpatrick, Rob; Seaman, Russell
ABSTRACT: Drought culminating in 2009 in the Murray–Darling Basin put severe downstream pressure on Lakes Alexandrina and Albert ("Lower Lakes") in South Australia. Falling water levels caused sulfidic acid sulfate soils (ASS) to dry forming sulfuric ASS (pH < 4) in lakebeds, along with environmental, economic and public health concerns. The pace of sulfuric ASS spread overwhelmed scientific efforts to develop robust hydrogeochemical models for the best management decisions. Meanwhile, community impatience grew because of fears for livelihoods, public health and loss of recreational amenity and exacerbated by apparent slow pace of government response caused by lagging scientific support. Responding to the looming problems, government, community and scientists joined in a citizen science project. The project comprised a programme of community ASS education, training and a field sampling programme conducted over four intervals (August 2009–June 2010). The project attracted 84 volunteers who sampled 51 survey areas covering the full range of ASS. The citizen scientists allowed a wider geographic and temporal sampling reach than was otherwise possible by scientists alone. The citizen scientists amplified the work of scientists by adding to the pool of data and freeing scientists to concentrate on non-routine ASS work. Perhaps of more enduring importance, the project showed how community, government and scientists can cooperate at times of environmental stress. The experience has grown government's capability to implement policy to grow community resilience during environmentally stressful episodes. Finally, the Lower Lakes community is now positioned for the next drought because community knowledge, leadership and networks are now in place.